PENATAAN LEMBAGA DALAM PENYELESAIAN SENGKETA HASIL PEMILIHAN KEPALA DESA BERDASARKAN PERATURAN PERUNDANG- UNDANGAN - Indah Septipah; Zulfikar Jayakusuma; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The 1945 Constitution of the Republic of Indonesia emphasizes that theIndonesian state is a unitary state divided into provinces, districts or cities. Article 18Bparagraph (2) of the 1945 Constitution of the Republic of Indonesia recognizes customarylaw community units and their traditional rights as long as they still exist and are inaccordance with the principles of the Unitary State of the Republic of Indonesia. The basicidea of Article 18B paragraph (2) is to give respect and recognition to villages that havetraditional rights or in other terms origin rights. Village administration is led by the villagehead. The village head is directly elected by the people as a form of democracy or villagepeople's sovereignty. However, this election has potential problems, one of which is thedispute over the results of the village head election. Law Number 6 of 2014 concerningVillages stipulates that disputes over village head election results are resolved by theRegent/Mayor. This has the potential not to solve the problem because it is not in accordancewith the original village autonomy. The principle of recognizing the origins of villagecommunities which is accommodated as the principle of independence in the Village Law isnot fully implemented in the articles. As evidence, there is still intervention or interferencefrom the district/city government in resolving disputes over the results of the Village Headelection which should be submitted to the Village through deliberations.This type of research is normative legal research because it uses literaturestudies in searching for data. This research is descriptive in nature which provides detaileddata on the existing problems. This study uses qualitative data analysis, which meansexplaining and concluding regarding the settlement of disputes over the results of villagehead elections based on laws and regulations and the form of arrangement of village headelection organizers. This study uses secondary data or scientific data that has been codified.The results of this study explain that first, the granting of authority to regional heads in orderto resolve disputes over village head election results will raise new problems. Second, thevillage head election dispute resolution model that prioritizes deliberations according to theprinciple of genuine village autonomy must be implemented by the government if it fails toproceed with the alternative of appointing a neutral third party and the second alternativethrough a special court. Third, strengthening the position by including village head electionsas one of the electoral regimes in Indonesia. Fourth, there is a need for ad hoc institutionalrestructuring of village head election organizers by including district KPU and districtBawaslu as part of the organizers.Keywords: Village Head Election, Disputes, Village Head Election Institutions